CSR Communication as a Game of Tetris: A systemic approach to sustain stakeholder trust - Kabir, Moutushi (2007)
The central idea behind this dissertation is to assert that a systemic or holistic approach to Corporate Social Responsibility (CSR) Communication is needed to make it effective.